Effect of Hydrocolloids on the Functional Properties of Batter Mix Used for the Preparation of Coated Shrimps - C.N., Ravishankar; Ninan, George; A.R., Abbas; A.C., Joseph (Fishery Technology, 2025)
In the present study, the effect of the addition of three different hydrocolloids viz. Guar Gum (GG), Carboxy Methyl Cellulose (CMC) andCarboxy Methyl Chitosan (CMT) onlRe functional properties of batter mix used for the preparation of coated shrimps was investigated. The maximum viscosity was noticed in batter containing GG at 1:2 dilution followed by batters containing CMC and CMT. Among the three batter systems, GG based batter showed highest shear thinning behavior and indicated maximum viscosity at lower dilutions and lower shear rates. Compared to the other two batters, GG based batter indicated maximum water retention capacity irrespective of temperatures and dilutions. In coated shrimps, the highest pick up was observed with GG-based batter, followed by CMC and CMT based batters. Thus, in terms of functional properties and batter consistency, GG based batter mix was found to be superior to the other two batter mixes.